Hepatocellular Carcinoma with Blood Supply from Parasitized Omental Artery: Angiographic Appearance And Chemoembolization - Gao, Song; Yang, Ren-jie; Dong, Jia-hong (Chinese Journal of Cancer Research; Vol 24, No 3 (September 01, 2012): Chinese Journal of Cancer Research, 2012)
Objective: To analyze angiographic appearance of hepatocellular carcinoma (HCC) with blood supply from parasitized omental artery (POA), and evaluate the technical feasibility, safety and therapeutic efficacy of chemoembolization via the POAs. Methods: A total of 1,221 HCC patients who had undergone chemoembolization procedures were evaluated retrospectively. The evaluated indexes included the incidence rate of POAs, success rate of superselective catheterization, post-reaction after chemoembolization, and the cumulative survival rates. Results: Totally 1,221 HCC patients had undergone 3,639 chemoembolization procedures, and 32 patients with POAs were enrolled, with 97 POAs found in 76 angiography procedures, giving an incidence rate of 2.09%. POA was observed mostly at the right lobe and left medial lobe except the segment II, and 62 POAs underwent superselective catheterization with microcatheter, giving a success rate of 63.9%. The angiographic appearance was: (1) hypertrophic POAs participating in tumor staining (n=28); (2) stiff and distorted POA (n=11), displaced due to tumor’s oppression (n=8); and (3) defective tumor staining close to either gastrocolic omentum distribution or liver capsule (n=7). In 19 patients, chemoembolization via POAs was performed successfully (A group), while the remaining 13 patients failed (B group). Except 1 acute edema pancreatitis case, no serious complication was recorded. The cumulative survival rates of 6-, 12-, 18- and 24-month were 78.9%, 47.4%, 31.6% and 21.1% respectively for A group; correspondingly, 61.5%, 30.8%, 15.4% and 7.7%% for B group, in which 2 patients died of ruptured HCC. Conclusion: Chemoembolization with microcatheter via POAs is a relatively safe, feasible and valuable method.